2021
DOI: 10.33736/ijbs.3740.2021
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of e-Commerce Adoption: Evidence from Small and Medium-Sized Enterprises in India

Abstract: Information technology (IT) is driving the business world in contemporary times. Large, medium, and small organisations in developed and developing countries are trying to adopt electronic commerce (e-commerce). Small and medium-sized enterprises (SMEs) are abundant in India, which is a rapidly developing country. Despite enormous efforts to adopt e-commerce, SMEs must address many hurdles. The major objective of this paper is to investigate the determinant factors that influence the adoption of e-commerce in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 29 publications
1
24
0
7
Order By: Relevance
“…When effective supervision has been performed, the company will be managed well where all available information will be disseminated by the management board (White et al, 2007). The independent board of commissioners is also considered as a tool to monitor behaviors of the board of directors (management), thus causing more voluntary disclosure of the company information (Huafang and Jianguo, 2007;Jasra et al, 2010;Rosenstein and Wyatt, 1990). This statement is supported by studies (Anggraini and Wulan, 2019;Khoirudin, 2013) which found results that independent board of commissioners has impact on ISR disclosure.…”
Section: 3mentioning
confidence: 94%
“…When effective supervision has been performed, the company will be managed well where all available information will be disseminated by the management board (White et al, 2007). The independent board of commissioners is also considered as a tool to monitor behaviors of the board of directors (management), thus causing more voluntary disclosure of the company information (Huafang and Jianguo, 2007;Jasra et al, 2010;Rosenstein and Wyatt, 1990). This statement is supported by studies (Anggraini and Wulan, 2019;Khoirudin, 2013) which found results that independent board of commissioners has impact on ISR disclosure.…”
Section: 3mentioning
confidence: 94%
“…Social media sites through the Android system are also one of the most popular promotional tools (Nurdiansyah, 2019). SMEs with an efficient infrastructure and organisational climate are more likely to adopt e-commerce (Sujatha & Karthikeyan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Competition is stiff among different companies, that is why companies are trying to search and attract talented employees across the globe. For this purpose, they are trying to adopt best diversity practices to improve their productivity and overall performance (Rehman, 2011).…”
Section: Introductionmentioning
confidence: 99%